If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13j + -9j + 15 = 3 Reorder the terms: 15 + 13j + -9j = 3 Combine like terms: 13j + -9j = 4j 15 + 4j = 3 Solving 15 + 4j = 3 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 4j = 3 + -15 Combine like terms: 15 + -15 = 0 0 + 4j = 3 + -15 4j = 3 + -15 Combine like terms: 3 + -15 = -12 4j = -12 Divide each side by '4'. j = -3 Simplifying j = -3
| 6p-2-3p=17 | | 3n+1-16-n=20 | | 16v+-4v+-14=10 | | 8x+8=6x+44 | | 14x=x^2 | | 2y-9=10y+55 | | 8x-(2x-8)=62 | | 4a-5b=5 | | 5x-(x+4)=5+4(x-2) | | a=5 | | -14v+7=-7 | | 19y+-y+2y=-20 | | 4x-80=180 | | 8+8y=-6+3y | | 5x-9y=2 | | 4x-80=120 | | y+15=-2(x-15) | | 10x-2(x+4)=8(x-2)+6 | | 8v+6=4v-2 | | x^2+1x+10= | | -9(-21)= | | (x^4+5y^5)(x^4-y^5)= | | x+(x+5)(-2)= | | (3v+5)(3c-5)= | | x+2v=w | | (5c-3)(6c-5)= | | R=-0.408 | | x-4(x+2)= | | 4x^3y+16x^2y+12xy= | | -3m=4.2 | | 53x^2-20x^4=18 | | -3+-5=36 |